BALO’NUN KONSANTRİK SKLEROZU: BİR OLGU SUNUMU - ÖZTÜRK MUNGAN, Semra; YENİ, Seher; KARAARSLAN, Ercan; KARAAĞAÇ, Naci (Cerrahpaşa Medical Journal, 2014)
Background.- Balo’s Concentric Sclerosis is a rapidly progressive rare disease with a fulminant course that affects young adults. The symptoms usually consist of aphasia, cognitive and behavioral disturbances. It is thought to be in the spectrum of demyelinating diseases. Observation.- In this article , a case diagnosed antemortem with clinical features and MRI findings. It is pointed out that signs and symptoms in Balo.s concentric sclerosis may be atypical and prognosis is not often fatal. In this current case report, we emphasized that antemortem diagnosis of Balo.s Concentric Sclerosis is possible and it does not always have a fulminant course as previously reported.